1984
DOI: 10.1246/cl.1984.1283
|View full text |Cite
|
Sign up to set email alerts
|

PREPARATION OF POROUS, AMORPHOUS, AND ULTRAFINE TiO2 PARTICLES BY CHEMICAL VAPOR DEPOSITION

Abstract: Ultrafine TiO2 particles were prepared by chemical vapor deposition of titanium tetraisopropoxide. The particle formation reaction, being catalyzed by the TiO2 deposit on the reactor wall, took place even at as low a temperature as 250°C, according to the stoichiometric relation of Ti(C3H7O) →TiO2 + 4C3H6 + 2H2O. The TiO2 particles were amorphous and porous, the specific surface area of which reached 300 m2/g.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 3 publications
1
21
0
Order By: Relevance
“…Table 1 have higher activation energy, so they will probably only occur at higher temperature. In our previous work, the onset temperature for the film growth was estimated to be around 550 K. [23] In the literature it has been reported that the onset temperature for the film growth depends on whether or not TiO 2 has been previously deposited; [11,32] for example Komiyama [33] observed that the onset temperature for the surface decomposition of TTIP was around 523 K, in reactors where TiO 2 has been deposited earlier, and 643 K in reactors that were clean. In previously reported work, based on IR measurements, precursor depletion near the substrate surface was observed and the gas-phase dissociation of TTIP was suggested to be a possible reason.…”
Section: Temperature and Homogeneous Reaction Ratesmentioning
confidence: 96%
“…Table 1 have higher activation energy, so they will probably only occur at higher temperature. In our previous work, the onset temperature for the film growth was estimated to be around 550 K. [23] In the literature it has been reported that the onset temperature for the film growth depends on whether or not TiO 2 has been previously deposited; [11,32] for example Komiyama [33] observed that the onset temperature for the surface decomposition of TTIP was around 523 K, in reactors where TiO 2 has been deposited earlier, and 643 K in reactors that were clean. In previously reported work, based on IR measurements, precursor depletion near the substrate surface was observed and the gas-phase dissociation of TTIP was suggested to be a possible reason.…”
Section: Temperature and Homogeneous Reaction Ratesmentioning
confidence: 96%
“…Two different chemical precursors have been used: titanium tetrachloride (TiCl 4 ) and titanium tetraisopropoxide (TTIP). Particles were synthesized by either oxidation of TiCl 4 (Suyama and Kato 1976;Morooka et al 1989;Akhtar et al 1991;Jang and Jeong 1995;and Windeler et al 1997), thermal decomposition of TTIP (Kanai et al 1985;Komiyama et al 1984;Okuyama et al 1986;Okuyama et al 1990), or hydrolysis of TTIP (Kashima and Sugiyama 1990). These investigations focused on the effect of reaction temperature, precursor concentrations, and residence time on either the primary particle or aggregate size.…”
Section: Chemical Pathways To Titanium Dioxide Formationmentioning
confidence: 99%
“…Two different chemical precursors have been typically used in these investigations namely, titanium tetra chloride (TiCl 4 ) and titanium tetra isopropoxide (TTIP). In high temperature processes, particles can be synthesized either by the oxidation of TiCl 4 (Suyama and Kato 1976;Morooka et al, 1989;Akhtar and Xiong, 1991;Akhtar and Vemury, 1994;Jang and Jeong, 1995;Yang et al, 1996;Yang et al, 1997;Windeler and Friedlander, 1997), or by the hydrolysis of TiCl 4 (Akhtar and Vemury,1994;Xia et al, 1999a,b) or by the thermal decomposition of TTIP (Komiyama and Kanai, 1984;Okuyama et al, 1986;Okuyama et al, 1990) or by the hydrolysis of TTIP (Wu et al, 1998;Kirkbir and Komiyama 1988;Chan et al, 1999). Recently, considerable interest has been directed towards the synthesis of titania at low temperatures based on aqueous phase processing (Kim and Park, 1999;Park et al, 1999;Li and Fan, 2002;Yin et al, 2002;Tang and Zhang, 2002;Yang, 2003).…”
Section: Introductionmentioning
confidence: 99%